Online gaming to find a new job: Examining job seekers' intention to use serious games as a self-assessment tool - Sven Laumer; Andreas Eckhardt; Tim Weitzel (Zeitschrift für Personalforschung (ZfP), 2012)
Serious games can be used as self-assessment tools in recruiting processes. We develop a model explaining jobseekers' intentions to use these applications, which help them to gain a realistic idea of the job at hand and allows them to submit their application only if the job truly fits their individual profile. Drawing on organizational justice theory and the technology acceptance literature, our model is empirically evaluated using data from 1,882 jobseekers. The results indicate that jobseekers' intention to use self-assessments is driven in particular by its perceived ease of use, perceived usefulness, perceived enjoyment, and perceived selection fairness. In contrast, the issue of privacy security has no significant impact on jobseekers' intentions. For firms, using serious games as a self-assessment tool can lead to a reduction in the total number of unsuitable applications they receive. – – Professionelle Online-Spiele werden primär in der Personalbeschaffung als ein Instrument zur Selbstselektion von Kandidaten eingesetzt. Sie bieten Stellensuchenden einen realistischen Eindruck der Anforderungen einer ausgeschrieben Stelle. Bei einer großen Übereinstimmung der eigenen Fähigkeiten mit den Anforderungen der offenen Stelle können sich Kandidaten dann bei dem betreffenden Unternehmen bewerben. Der vorliegende Beitrag entwickelt in diesem Zusammenhang basierend auf Forschungsarbeiten aus dem Bereich der Technologieakzeptanz ein Forschungsmodell, um die Intention von Stellensuchenden zur Nutzung derartiger Anwendungen zu erklären. Mit Hilfe einer empirischen Studie, an der sich 1.882 Stellensuchende beteiligt haben, wird gezeigt, dass für die Intention zur Nutzung von professionellen Online- Spielen, die wahrgenommene Einfachheit der Nutzung, die Nützlichkeit des Online- Spiels, der Spaß bei der Nutzung sowie die wahrgenommene Fairness des Selektionsinstruments signifikante Einflussfaktoren sind.
Keywords: M12; M15; 650; serious gaming; self-assessment; technology acceptance; e-recruiting; applicant selection; Personalbeschaffung; Personalauswahl; Computerspiel; Selbstevaluation; Elektronisches Personalmanagement